ナンキョク ペネトレーター ノ インターフェイス ソフトウェア ノ カイハツ - 渋谷, 和雄; シブヤ, カズオ; Shibuya, Kazuo (2005)
P(論文) 南極域での人工地震探査に使用する投下式地震計(南極ペネトレーター)センサー(GSS)をヘリコプター上の制御装置(ADCS)を通じてコマンド制御するために,タッチパネルディスプレーを持つ,パーソナルコンピューター(PC)上で動作するインターフェイス・ソフトウェアを開発した.PCパネルの設定画面上でコンボックスボタンをペンタッチし,各種設定やコマンドを実行する.インターフェイス・ソフトウェアが行う基本的な操作はGSS時計のUTC時刻同期,観測スケジュールファイルの作成と送信,GSS時計の較正,メモリーデータの読み出しである.コマンドの実行ログファイルが自動生成される.無線機ONの状態では電力を著しく消費するので,コマンド送受信/データ回収を行わない一定期間,無線機をOFFにして待機状態に入るsleep機能を持っている.通信に時間のかかる時刻較正,データ読み出しについては,実行状況を処理待ち受けダイアログで表示し,正常に機能しているかどうか目視的に判断する.第43次隊の運用においては,指定日時になっても無線モデムに電源が入らないため無線リンクが取れない,という不具合が指摘された.また,年をまたぐスケジュールをセットした時,新年以後のスケジュールが起動しなかった.これらソフトウェアに関する不具合について原因を究明し,対策を行い解決した. We have developed PC-based interface software which controls ground system segments (GSSs) of the Antarctic penetrator through an automatic data collection system onboard a helicopter. A pen-touch panel was developed for easy operation. There are six basic functions in the interface software; GSS time synchronization", make schedule file", send schedule file", GSS time calibration", data read-out", and sleep". The sleep command enables us to cut off the radio transmitter/receiver to save power during a pre-determined period. After execution of each command, log files are saved automatically. In order to monitor processing by eye, a bar graph appears during execution of time synchronization" and data read-out". As for malfunctioning encountered during the 43rd Japanese Antarctic Research Expedition, the related software bugs were identified and the codes were rewritten. departmental bulletin paper